The complete mitogenome of the bluespotted ribbontail ray Taeniura lymma (Forsskål, 1775) (Elasmobranchii: Myliobatiformes: Dasyatidae). (2nd September 2016) - Austin, Christopher M.; Tan, Mun Hua; Croft, Laurence J.; Meekan, Mark G.; Gan, Huan You; Gan, Han Ming
Abstract: The complete mitogenome of the ray Taeniura lymma was recovered from genome skimming using the HiSeq sequencing system. The T. lymma mitogenome has 17, 652 base pairs (59.13% A + T content) made up of 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs and a 1906 bp non-coding AT-rich region. This mitogenome sequence is the second for a ray from Australian waters, the first for the genus Taeniura and the ninth for the family Dasyatidae.